2010
DOI: 10.2522/ptj.20090035
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Muscle Strength Relates to Self-Reported Stooping, Crouching, or Kneeling Difficulty in Older Adults

Abstract: Decreased muscle strength, particularly when normalized for body size, predicts SCK difficulty. These data emphasize the importance of strength measurement at multiple levels in predicting self-reported functional impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 36 publications
0
57
0
2
Order By: Relevance
“…This finding is significant because of the role of quadriceps strength in daily function. Quadriceps weakness negatively effects mobility [14,15,28], which may help explain why other researchers have found difficulties with functional performance after THA. Despite the fact that significant functional differences were not seen in our data, possibly related to small sample size, several studies have confirmed the presence of functional deficits and difficulty walking after THA.…”
Section: Discussionmentioning
confidence: 90%
“…This finding is significant because of the role of quadriceps strength in daily function. Quadriceps weakness negatively effects mobility [14,15,28], which may help explain why other researchers have found difficulties with functional performance after THA. Despite the fact that significant functional differences were not seen in our data, possibly related to small sample size, several studies have confirmed the presence of functional deficits and difficulty walking after THA.…”
Section: Discussionmentioning
confidence: 90%
“…Some activities of daily life, such as shopping and cleaning the house, involve the ability to climb and descend steps, incline, crouch, and kneel down (3,17,29). Limitations in performing these functions considerably restricts the elderly's life activity and social participation (3,17).…”
Section: Discussionmentioning
confidence: 99%
“…Many motor skills are neglected during the process of aging, restricting daily life activities (3,18). Considering that falls present a multifactorial range (9), the concern with the fear of falling in elderly people exponentially limits the performance of usual tasks that demand multiple interactions of the sensorimotor system (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations